The Influence of Literacy, Religious Knowledge and Attitudes on Public Interest in Rahn Products - Putri, Putri; Junaidi, Junaidi; Ramadhan, Abid (LP3M Universitas Putra Bangsa, 2023)
This research aims to determine the factors influencing knowledge, literacy, religion, and attitudes toward public interest in Rahn products at Sharia pawnshops. 145 Pegadaian Syariah (Pawnshop) consumers were invited to this study through an online survey. SEM (Structural Equation Modeling) was used to examine research hypotheses. This study found that financial literacy, religiousness, and attitudes play important roles in influencing Pegadaian Syariah consumer preference. It means that consumers’ interest in Sharia pawnshops is because they influence individual understanding, knowledge, values, ​​and beliefs in Sharia-based financial products.